Styl życia pacjentów z nadciśnieniem tętniczym = Lifestyle in the patients suffering from hypertension - Beata Kropornicka; Bożena Baczewska; Ewelina Szalast; Ewa Krzyżanowska; Robert Łuczyk; Elżbieta Nowicka; Cecylia Olszak; Bożena Muraczyńska; Regina Lorencowicz (Kazimierz Wielki University, 2016)
Kropornicka Beata, Baczewska Bożena, Szalast Ewelina, Krzyżanowska Ewa, Łuczyk Robert, Nowicka Elżbieta, Olszak Cecylia, Muraczyńska Bożena, Lorencowicz Regina. Styl życia pacjentów z nadciśnieniem tętniczym = Lifestyle in the patients suffering from hypertension. Journal of Education, Health and Sport. 2016;6(12):338-352. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.200327 http://ojs.ukw.edu.pl/index.php/johs/article/view/4062         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 12.12.2016.       Styl życia pacjentów z nadciśnieniem tętniczym Lifestyle in the patients suffering from hypertension   Beata Kropornicka1, Bożena Baczewska1, Ewelina Szalast, Ewa Krzyżanowska1, Robert Łuczyk1, Elżbieta Nowicka1,Cecylia Olszak1,Bożena Muraczyńska2, Regina Lorencowicz3   1Katedra Interny z Zakładem Pielęgniarstwa Internistycznego Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 1 Department of Internal Medicine with the Department of Internal Nursing, Faculty of Health Sciences, Medical University of Lublin 2Katedra Chirurgii i Pielęgniarstwa Chirurgicznego Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 2 Department of Surgery and Surgical Nursing, Faculty of Health Sciences, Medical University of Lublin 3Katedra i Zakład Pielęgniarstwa Neurologicznego Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 3 Department of Neurological Nursing Faculty of Health Sciences, Medical University of Lublin   Streszczenie Wstęp. Nadciśnienie tętnicze jest najbardziej rozpowszechnionym czynnikiem ryzyka chorób układu krążenia. Celem pracy była ocena stylu życia pacjentów z nadciśnieniem tętniczym. Materiał i metoda. Badaniami objęto 101 chorych na nadciśnienie tętnicze. Badania prowadzono w Poradni Kardiologicznej i Poradni Nadciśnienia Tętniczego w Wojewódzkim Szpitalu Specjalistycznym i w Poradni Kardiologicznej Polikliniki Samodzielnego Publicznego Szpitala Klinicznego nr 4 w Lublinie w 2015 roku. Metodą wykorzystaną w pracy był sondaż diagnostyczny, techniką ankietowanie a narzędziem badawczym Inwentarz Zachowań Zdrowotnych autorstwa Juczyńskiego. Wyniki badań. Najkorzystniejsze postawy respondentów dotyczyły zachowań profilaktycznych. Najniższe wyniki badani uzyskali w kategorii prawidłowe nawyki żywieniowe. Wnioski. Badana grupa prezentowała głównie pozytywne zachowania zdrowotne. Płeć, miejsce stałego pobytu, wykształcenie nie miały istotnego wpływu na styl życia badanych. Natomiast źródło dochodów i wiek wpływały na styl życia respondentów.   Słowa kluczowe: styl życia , nadciśnienie tętnicze   Abstract Backgroud. Hypertension is the most common risk factor for cardiovascular diseases. The purpose of study was to assess the lifestyle in the patients with hypertension. Material and methods. The investigation was carried out in the group of 101 patients suffering from hypertension. The respondents were treated in the Outpatient Cardiological Clinic and the Outpatient Hypertension Clinic,RegionalSpecialistHospital inLublin, and the Outpatient Cardiological Clinic PSK-4 inLublin in 2015. The patients were diagnostically surveyed by means of a questionnaire technique using Juczyński's Health Behaviors Inventory (HBI). Results. The most advantageous attitudes were within the area of prophylactic behaviors, whereas the lowest were noted within proper eating habits. Conclusions. The results revealed positive health behaviors. The factors such as gender, place of permanent stay, or education did not affect the lifestyle of the respondents. However, the source of income and age exerted certain influence upon the lifestyle of the respondents.   Key words: lifestyle, hypertension